A new genus of Cophomantini, with comments on the taxonomic status of Boana liliae (Anura: Hylidae) - Pinheiro, Paulo D. P. [UNESP]; Kok, Philippe J. R.; Noonan, Brice P.; Means, D. Bruce; Haddad, Celio F. B. [UNESP]; Faivovich, Julian (Oxford Univ Press, 2019)
The non-monophyly of both the genus Myersiohyla and the Boana punctata group has been recovered in a number of published phylogenetic analyses. In this paper we report on the analysis of sequences of Boana liliae, a species originally assigned to the B. punctata group, in a dataset of Cophomantini that recovered novel phylogenetic relationships for this hylid tribe. Our results reveal Myersiohyla to be paraphyletic with respect to B. liliae. Support for the placement of Myersiohyla kanaima is poor, but this taxon is recovered as the sister taxon of the other Cophomantini genera (excluding Myersiohyla) or as the sister taxon of the remaining species of Myersiohyla (including B. liliae). These results lead us to propose two taxonomic changes in order to remedy the paraphyly of Myersiohyla: (1) a new genus is described for M. kanaima, and (2) Boana liliae is transferred to Myersiohyla. We further provide notes on the natural history and vocalizations of the new monotypic genus, a new diagnosis of the former B. liliae in the context of Myersiohyla, and discuss the evolution of tadpole morphology and biogeography of the earlier diverging clades of Cophomantini.
Keywords: Cophomantini; Hylidae; Myersiohyla; systematics